Isolation and Preliminary Characterization of a Vitamin K Dependent Peptide from Human Prothrombin - Elion, J; Benarous, R; Labie, D (Thrombosis and Haemostasis, 1976)
A peptide containing the vitamin K dependent Ca2+ binding region of human prothrombin has been isolated by adsorption of the tryptic digest of the native protein on barium citrate. Its aminoacid composition has been determined. The N- and C-terminal residues have been characterized. The obtained results are showing some slight differences with the corresponding bovine peptide. Since they were not strictly identical for two different preparations, the eventuality of a molecular heterogeneity is discussed.